System for the Introduction of Information systems to Higher Education Administrations Conforming to the Bologna Process - Mateljan, Vladimir; Drenovac, Sergej; Đambić, Goran (2008)
The Bologna process has introduced a whole range of new developments into the existing processes in higher education administrations – students receive ECTS points for each finished course and a certain number of ECTS points is required for the enrollment into each semester. ECTS points for each course are awarded based on the activities performed during the course: homework, lectures, seminars, oral and written examinations and other activities. This highlights the need for every higher education institution to adapt to the Bologna process either by modification of the existing information systems, or the introduction of the new ones. IVA system for information technology management of the higher education administrations is a new system developed in 2007, with the goal of enabling the management of data about students, courses, professors and study programs in line with the requirements of the Bologna process. With the introduction of IVA system, higher education institutions can realize savings with the rationalization and reduction of the amount of administrative tasks and the creation of new services with quicker and easier access to updated information and the increase in quality and reliability of the issued documents. Since the system is also designed to be a data repository, it supports the decision-making process in the institution by creating, or facilitating the access to qualitative and quantitative insight into the performance efficiency of particular business processes.
Projekt MZOS
Projekt MZOS
ENG